2023
DOI: 10.1002/adbi.202200240
|View full text |Cite
|
Sign up to set email alerts
|

The Actin Crosslinker Fascin Regulates Cell Chirality

Abstract: The left–right (L‐R) asymmetry of the cells, or cell chirality, is a well‐known intrinsic property derived from the dynamic organization of the actin cytoskeleton. Cell chirality can be regulated by actin‐binding proteins such as α‐actinin‐1 and can also be mediated by certain signaling pathways, such as protein kinase C (PKC) signaling. Fascin, an actin crosslinker known to mediate parallel bundling of actin filaments, appears as a prominent candidate in cell chirality regulation, given its role in facilitati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 39 publications
0
1
0
Order By: Relevance
“…For example, cell membranes are formed by chiral amphiphiles, collagen is formed from chiral helical fibers, and the widely cited double helix in genetic material is also chiral. In addition, cell chirality is also present, which can be regulated by actin-binding proteins such as α-actinin and can also be mediated by certain signaling pathways [11,15]. Recently, research suggested that the chiral moieties present on the material's surface have a great impact on their interaction with biological systems [16][17][18][19].…”
Section: Chiral Interface For Controlling the Cell Fatementioning
confidence: 99%
“…For example, cell membranes are formed by chiral amphiphiles, collagen is formed from chiral helical fibers, and the widely cited double helix in genetic material is also chiral. In addition, cell chirality is also present, which can be regulated by actin-binding proteins such as α-actinin and can also be mediated by certain signaling pathways [11,15]. Recently, research suggested that the chiral moieties present on the material's surface have a great impact on their interaction with biological systems [16][17][18][19].…”
Section: Chiral Interface For Controlling the Cell Fatementioning
confidence: 99%